Vrou as beeld van God, Deel 1: "n Historiese ondersoek - Vanaf Genesis tot die Middeleeue - Dreyer, Yolanda (Hervormde teologiese studies, 2000)
Woman created in the image of God, Part 1: a historical investigation - from Genesis to the Middle Ages. This study indicates that the traditions in the Pentateuch, especially the creation traditions, implied the egalitarian status of man and woman as image of God. The context of this traditions, however, was patriarchal and thus opened the possibility of the exploitation of women. Though Genesis 1:27 does not specifically attest to the asymmetry between man and woman in patriarchal society, the fate of women in general was bound up with the presentation of God as a male creator. The implications of this presentation can be clearly seen in texts of the intertestamental period. The study points out the degree to which Philo's view of a hierarchy concerning man and woman as immanent to God's order of creation, strongly influenced Christian thought on the place of women. Since the "fall of woman" necessitates a "soteriology", women in general are portrayed negatively in patristic texts. Mary is seen as the positive counterpart of Eve. The image of women then becomes that of submission on account of their alienation from God. The article concludes with the view of Thomas Aquinas that the subservience of slaves is less than that of women, because in their case it is not an order of creation.